Sexagesimal scale for mapping human genome Escala sexagesimal para mapear el genoma humano - RICARDO CRUZ-COKE (Revista Chilena de Historia Natural, 2001)
In a previous work I designed a diagram of the human genome based on a circular ideogram of the haploid set of chromosomes, using a low resolution scale of Megabase units. The purpose of this work is to draft a new scale to measure the physical map of the human genome at the highest resolution level. The entire length of the haploid genome of males is deployed in a circumference, marked with a sexagesimal scale with 360 degrees and 1296000 arc seconds. The radio of this circunference displays a semilogaritmic metric scale from 1 m up to the nanometer level. The base pair level of DNA sequences, 10-9 of this circunsference, is measured in milliarsec unit (mas), equivalent to a thousand of arcsecond. The "mas" unit, correspond to 1.27 nanometers (nm) or 0.427 base pair (bp) and it is the framework for measure DNA sequences. Thus the three billion base pairs of the human genome may be identified by 1296000000 "mas" units in continous correlation from number 1 to number 1296000000. This sexagesimal scale covers all the levels of the nuclear genetic material, from nucleotides to chromosomes. The locations of every codon and every gene may be numbered in the physical map of chomosome regions according to this new scale, instead of the partial kilobase and Megabase scales used today. The advantage of the new scale is the unification of the set of chromosomes under a continous scale of measurement at the DNA level, facilitating the correlation with the phenotypes of man and other species En un trabajo anterior yo diseñé un diagrama del genoma humano basado en un ideograma circular del conjunto haploide de cromosomas, usando una escala de baja resolución en megabases. El propósito de este trabajo es el de diseñar una nueva escala para medir el mapa físico del genoma humano al más alto nivel de resolución. La longitud completa del genoma haploide del varon es extendido en una circunsferencia, marcada con una escala sexagesimal de 360 grados y 1296000 segundos de arco. El radio de esta circunsferencia expone una escala métrica semiologarítmica desde 1 m hasta el nivel del nanometro. El nivel de bases pares de las secuencias del ADN de esta circunsferencia es medida en unidades milliarsec, "mas", equivalente a una milesica de segundo de arco. La unidad más equivalente a 1.27 nanómetro (nm) o 0.427 pares de bases (pb), y es el bastidor para medir las secuencias del ADN. Así, los 3 millardos de pares de bases del genoma humano pueden ser identificados por 129000000 unidades "mas" en continua correlación desde el número 1 al número 1296000000. Esta escala sexagesimal cubre todos los niveles del material genético nuclear desde los nucleotidos hasta los cromosomas. Las localizaciones de cada codon y de cada gen pueden ser numerados secuencialmente en las regiones cromosómicas del mapa físico del genoma, de acuerdo con esta nueva escala, en vez de usar las escalas parciales de kilobases y de megabases usadas actualmente. La ventaja de esta nueva escala es la unificación del conjunto de cromosomas bajo una continua escala correlativa de medidas a nivel del ADN, facilitando la correlación con los fenotipos del ser humano y otras especies